Pengaruh Pemberian Konsentrat Mengandung Tepung Binahong Terhadap Biokimia Darah Domba Ekor Gemuk - Asri Apriana Widu (Lembaga Pengembangan Kinerja Dosen, 2025)
This study was conducted to evaluate the impact of adding binahong flour in concentrate on the blood biochemical parameters of fat-tailed sheep. The study used a Completely Randomized Design with 16 experimental units divided into 4 treatments and 4 replications. The treatments given were: R0 (control feed), R1 (10% binahong flour), R2 (20%), and R3 (30%). The average results of blood plasma glucose analysis (mg/dl): R0 83.08±4.85, R1 85.62±,4.47 R2 88.46±1.69, R3 88.92±2.26. For Blood Plasma urea (mg/dl) R0 43.55±2.96, R1 46.69±1.28, R2 46.87±3.35, R3 47.36±3.10. Meanwhile, for blood cholesterol (mg/dl) R0 200.50±2.13, R1 192.18±17.44, R2 190.51±19.68, R3 190.43±2.36. The results of statistical tests showed that the treatment had a very significant impact (P<0.01) on blood glucose, blood plasma urea and blood cholesterol in sheep. The conclusion is that the use of binahong flour up to 30% in the concentrate has the potential to increase glucose levels, blood plasma urea, and reduce cholesterol levels in fat-tailed sheep.